Rates of delirium associated with calcium channel blockers compared to diuretics, renin-angiotensin system agents, and beta-blockers: an electronic health records network study - Harrison, P; Luciano, S; Colbourne, L (SAGE Publications, 2020)
Background: Antihypertensive drugs (AHTs), especially calcium channel blockers (CCBs), have been associated with differential rates of a number of neuropsychiatric outcomes. Delirium is commonly attributed to medication, including AHTs, but delirium incidence has not been compared directly between AHT classes.